Performance of EEDR Routing Protocol under Various Path Loss Models for WSNs - M S, Pramod; ., Shivashankar (International Journal of Engineering and Technology, 2018)
Path loss is the power variation between the receiver power and the transmitter power. The attenuation of the signal takes place in Wireless Sensor Networks (WSNs) because of path loss. There are various kinds of path loss due to absorption, reflection, refraction and many other factors under diverse environments which are all defined under path loss models. This research paper provides a brief study on different path loss models and their mathematical evaluation. The objective of the proposed work is to evaluate the Energy Efficient Distributed Receiver (EEDR) based routing protocol under the various path loss models and check the performance variation in different environments. The simulation results shows the effect of path loss on end-to-end delay, number of hops, energy consumption and the number of alive nodes in WSNs topology.Â Â Â